2007
DOI: 10.1002/ijc.23020
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral homogeneity of MGMT promoter hypermethylation as demonstrated in serial stereotactic specimens from anaplastic astrocytomas and glioblastomas

Abstract: -Heine-Universit€ at D€ usseldorf, D€ usseldorf, GermanyHypermethylation of the DNA repair gene O 6 -methyl-guanine DNA methyltransferase (MGMT) has been linked to prolonged survival in glioblastoma patients treated with alkylating agents. It was aimed to analyze prospectively whether the MGMT status of malignant gliomas could be determined from small-sized stereotactic biopsies (maximum volume: 1 mm 3 ). Special attention was directed towards the intratumoral distribution of the MGMT promoter methylation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 12 publications
4
114
2
Order By: Relevance
“…Unlike the MSP assay used in the majority of clinical studies, pyrosequencing allows highly reproducible quantitative evaluation of methylation at discrete CpG sites thereby providing more information on promoter methylation status and facilitating analysis of specific methylation patterns. Analysis is fast and cost effective and, unlike conventional bisulphite sequencing (Grasbon-Frodl et al, 2007;Mikeska et al, 2007;Parkinson et al, 2008), is practical in a diagnostic environment. In our assay, the PCR primers are methylation independent and as little as 5% methylated DNA in a mixture of methylated and unmethylated DNA may be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the MSP assay used in the majority of clinical studies, pyrosequencing allows highly reproducible quantitative evaluation of methylation at discrete CpG sites thereby providing more information on promoter methylation status and facilitating analysis of specific methylation patterns. Analysis is fast and cost effective and, unlike conventional bisulphite sequencing (Grasbon-Frodl et al, 2007;Mikeska et al, 2007;Parkinson et al, 2008), is practical in a diagnostic environment. In our assay, the PCR primers are methylation independent and as little as 5% methylated DNA in a mixture of methylated and unmethylated DNA may be detected.…”
Section: Discussionmentioning
confidence: 99%
“…18 Third, many authors have failed to identify a correlation between MGMT promoter methylation assessed by MSP and protein levels in glioma tissue assessed by immunochemistry. 18,[24][25][26] One explanation for this lack of correlation is the considerable and highly variable contamination of glioma tissue sections with non-neoplastic cells expressing MGMT that are not always easy to distinguish from tumor cells (Figure 3). …”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Stereotactic biopsies should be controlled for tumor content, and usually only yield sufficient DNA when obtained frozen. 25 Tissues should be fixed in buffered formalin. Overfixation decreases the quality of the DNA owing to formation of cross-links, and can impede successful testing.…”
Section: Mrna Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating MGMT promoter methylation within glioblastoma lesions as well as in paired primary and recurrent glioblastoma samples suggested that MGMT promoter methylation could be a homogeneous marker throughout malignant gliomas (48) and that most recurrent lesions retained the methylation profile from the primary lesions (49). However, considering the increasing awareness of tumor heterogeneity (50) and the positive predictive value (77%) for serum assay observed in our study, the serum methylation assay may provide a possible alternative for patients with no available tumor samples.…”
Section: Discussionmentioning
confidence: 99%